Measurment systems : - Doebelin, Ernest O. (McGraw-Hill / Irwin, 2004)
Measurement Systems: Application and Design provides a breadth/depth of coverage not found elsewhere. This allows easy selection of topics to meet local needs for beginning or advanced courses, and continued value for industrial practice. It treats measurement science and technology as an important field in its own right, starting with basic principles, applying them to sensors for physical variables, and completing the measurement chain with signal conditioning and data acquisition/processing hardware and software. Carefully selected references and websites lead the interested reader to resources beyond the scope of the text. Descriptive material is buttressed with detailed analysis/design information. Helpful software (statistics, dynamic simulation, data acquisition/processing) is integrated throughout. Book jacket.